P3.84 Estimating the antibody prevalence of herpes simplex virus type 1 among select middle east and north africa populations. (8th July 2017) - Nasrallah, Gheyath; Dargham, Soha; Mohammed, Layla; Abu-Raddad, Laith
Abstract : Introduction: Evidence indicates a growing role for herpes simplex virus type-1 (HSV-1) as a sexually transmitted infection and as the etiological agent of genital herpes, but HSV-1 epidemiology in the Middle East and North Africa (MENA) remains poorly understood. We aimed to measure HSV-1 antibody prevalence among select MENA populations and to characterise the infection's age-distribution. Methods: Evidence indicates a growing role for herpes simplex virus type-1 (HSV-1) as a sexually transmitted infection and as the etiological agent of genital herpes, but HSV-1 epidemiology in the Middle East and North Africa (MENA) remains poorly understood. We aimed to measure HSV-1 antibody prevalence among select MENA populations and to characterise the infection's age-distribution. Results: Country-specific HSV-1 prevalence was estimated for 10 MENA national populations of male blood donors residing in Qatar. HSV-1 prevalence was estimated at 97.5% (95% confidence interval (CI) 95.3%–98.7%) among Egyptians, 92.6% (95% CI 87.2%–95.8%) among Yemenis, 90.7% (95% CI 84.5%–94.6%) among Sudanese, 88.5% (95% CI 83.9%–92.6%) among Syrians, 86.5% (95% CI 81.0%–90.5%) among Jordanians, 82.3% (95% CI 78.2%–85.7%) among Qataris, 81.4% (95% CI 73.3%–87.5%) among Iranians, 81.4% (95% CI 73.4%–87.4%) among Lebanese, 80.5% (95% CI 74.2%–85.2%) among Palestinians, and 77.0% (95% CI 70.7%–82.3%) among Pakistanis. Age-specific HSV-1 prevalence was estimated among male blood donors from Egypt, the Fertile Crescent (Iraq, Jordan, Lebanon, Palestine and Syria) and Qatar. There was a trend of growing HSV-1 prevalence with age among the Fertile Crescent and Qatari nationals. HSV-1 prevalence increased from 70.0% (95% CI 56.3%–80.9%) for those aged <24 years up to 98.0% (95% CI 89.5%–99.7%) for those aged ≥55 years in the Fertile Crescent. Similar pattern was observed for Qatar, but for Egypt, prevalence was steadily above 90% for all age groups. Our results showed no significant association between sex and HSV-1 seropositivity. Conclusion: HSV-1 prevalence in MENA continues at high level, but for the majority of nationalities, at considerably lower levels than historical levels. The decline in prevalence is most pronounced among youth. As much as a third of those <30 years of age are reaching sexual debut with no protective antibodies against HSV-1 genital acquisition, and accordingly, are at risk of genital herpes.